(untitled) (Hematology Meeting Reports, 2009)
Alternative genetic pathways for t-MDS and t-AML were previously suggested based on characteristic chromosome aberrations identical with those observed in de novo MDS and AML. The recurrent balanced translocations and inversions of these diseases in most cases result in chimeric rearrangement and inactivation of genes for hematopoietic transcription factors (class II mutations) which disturb cellular differen-tiation. Recently, activating point mutations or internal tandem duplications of genes for signal transduction in the receptor tyrosine kinase – RAS/BRAF pathway (class I mutations) have gained interest in de novo MDS and AML. A synergism between class I and class II mutations in the development of AML has been suggested. This hypothesis is now supported by our investigations of 140 unselected patients with t-MDS or t-AML for class I and class II mutations. A clustering of class I mutations in the different genetic pathways support the model for leukemic transformation.